1977
DOI: 10.1203/00006450-197706000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Serial Measurements of Serum Calcium, Magnesium, Parathyroid Hormone, Calcitonin, and 25-Hydroxy-Vitamin D in Premature and Term Infants during the First Week of Life

Abstract: CONCLUSIONPercutaneous absorption of testosterone from the ventral forearm in newborn rhesus monkeys was determined as a mcasure of skin barrier function. Skin absorption at a concentration of 4 and 40 pg/cm2 were, respectively, 22.5 r 2.2% (SD) and 6.8 r 2.1% of the applied dose, values which were not significantly different ( P > 0.05) from those of adult rhesus and which were similar to man. If the absorption is expressed as micrograms absorbed systemically, then the amounts are 0.9 and 2.7 pg/cm2 area of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
40
1
2

Year Published

1978
1978
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(55 citation statements)
references
References 15 publications
12
40
1
2
Order By: Relevance
“…The concomitant increases in 1,25-(OH)2D and plasma Ca during the first week of life in our infants lends further support to the notion that vitamin D metabolism is of importance in the perinatal adjustment of mineral homeostasis. The lack of significant correlation between simultaneous 1,25-(0H)zD and Ca levels suggests, however, that other factors such as parathyroid function or Ca intake are also important (20,29).…”
Section: Resultsmentioning
confidence: 98%
“…The concomitant increases in 1,25-(OH)2D and plasma Ca during the first week of life in our infants lends further support to the notion that vitamin D metabolism is of importance in the perinatal adjustment of mineral homeostasis. The lack of significant correlation between simultaneous 1,25-(0H)zD and Ca levels suggests, however, that other factors such as parathyroid function or Ca intake are also important (20,29).…”
Section: Resultsmentioning
confidence: 98%
“…On that basis, they concluded Al in the vaccines is safe. Hillman et al [161] found that parathyroid hormone is elevated in pre-term and full-term infants at 48 hours and up to 7 days. The pre-term infants had higher PTH than full term infants.…”
Section: Mechanism Of Impaired Excretion Of Aluminummentioning
confidence: 99%
“…Late NH occurs after 1st week of life, usually symptomatic and requires long-term calcium therapy. [4][5][6] Another entity, resistant or prolonged hypocalcemia is defined as symptomatic hypocalcemia not responding to appropriate doses of calcium supplementation, calcium requirement beyond 72 h of age in neonates orhypocalcemia manifesting beyond 1st week of life. 1 The index case in this report is of late onset variety.…”
Section: Discussionmentioning
confidence: 99%
“…1 The early NH usually manifests within 72 hours after birth, requiring short term calcium supplementation, and it is a frequent co morbidity in high risk neonates. Maternal diabetes, prematurity and Perinatal asphyxia 1,[4][5][6][7] are the important causes of early NH. Late NH occurs after 1st week of life, usually symptomatic and requires long-term calcium therapy.…”
Section: Discussionmentioning
confidence: 99%